Integrated transcriptomics and metabolomics reveal multi-target mechanisms of tannins against Clostridium perfringens and necrotic enteritis - Huiping Xu; Lu Gong; Yuming Guo (Journal of Animal Science and Biotechnology)
Abstract Background Clostridium perfringens is a pathogen that secretes multiple toxins, impacting humans and animals. It can cause intestinal diseases such as necrotic enteritis. Although tannins inhibit C. perfringens proliferation, the precise underlying mechanisms are unclear. Objective This study integrated transcriptomics and metabolomics to systematically investigate the mechanism by which tannins, specifically pentagalloylglucose (PGG) and tannic acid (TA), inhibit C. perfringens and potential pathways to alleviate infection in vivo. Results Ion concentration measurements, flow cytometric analysis, and transmission electron microscopy revealed that PGG and TA damaged the cell membrane structure of C. perfringens, triggering cytoplasmic content leakage. Additionally, PGG and TA significantly affected C. perfringens at the transcriptional and metabolic levels. Bioinformatics analysis revealed that PGG and TA induced amino acid restriction, disrupted energy metabolism, and impeded the ability of C. perfringens to sense and respond to the external environment. In an in vitro C. perfringens-infected intestinal cell model, PGG and TA bound α toxin, significantly reduced the mRNA expression of inflammatory factors, and improved intestinal barrier function and cell viability. Compared to PGG, TA exhibited stronger inhibitory activity against C. perfringens and binding to α toxin. In vivo, PGG and TA alleviated C. perfringens-induced weight loss in mice, improved intestinal villi morphology, and reduced intestinal inflammation and tight junction gene dysregulation. Conclusion These findings indicate that tannins inhibit C. perfringens, improve gut tissue integrity and reduce inflammation, demonstrating their multi-target effects of resisting intestinal diseases caused by harmful bacteria. This offers new insights for plant polyphenol-based strategies against necrotic enteritis. Graphical Abstract